SECURITIZATION OF IDENTITY IN TURKEY DURING THE AKP ERA - Aydindag, Didem; Isiksal , Huseyin (Revista Gênero e Interdisciplinaridade, 2021)
This article analyses some of the key political discussions in Turkey, which are identity dichotomy, securitization and desecuritization cycle of religion under the rule of the Justice and Development Party particularly in the post-2007 period. The article argues that mostly from 2007 onwards, the ruling party started the de-securitization process of religion as a referent object. The article further points out that from 2014 onwards a shift in threat perception can be analyzed utilizing anti-Westernization. The West interchangeable meant and homogenized as the Christian world, is framed as Islamophobic and therefore the new threat to Islamic identity is not coming from the domestic secular identity but from the outside, the Western Christian identity/civilization. The conceptualization of the theoretical framework is built upon the Copenhagen School’s societal securitization aspect. The first part focuses on the Copenhagen School of security in general and identity securitization in particular. The latter sections evaluate the transformation of religious and secular identities through securitization and counter securitization by certain segments of the public. The transformation is analyzed through the ruling periods of the AKP. The data consists of the AKP party manifestos, official reports, election campaigns and speeches given by former Prime Minister and current President Recep Tayyip Erdoğan between the periods of 2002-2019.